2014
DOI: 10.1002/uog.12555
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of shear wave speed in the human uterine cervix

Abstract: Objectives Our goals were to explore the spatial variability within the cervix and the sensitivity of shear wave speeds (SWS) to assess softness/stiffness differences in ripened (softened) versus unripened tissue. Methods We obtained SWS estimates from hysterectomy specimens (n=22), a subset of which were ripened (n = 13). Multiple measurements were made longitudinally along the cervical canal on both the anterior and posterior sides of the cervix. Statistical tests of differences in the proximal vs. distal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
97
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(108 citation statements)
references
References 47 publications
9
97
1
1
Order By: Relevance
“…This technique, in which strain maps of tissues are calculated after applying static stress directly onto the surface of the body with the ultrasonic probe, provides information on the relative stiffness of the tissues investigated, but is highly operator dependant and non-quantitative. Such drawbacks can be overcome by using dynamic elastography techniques [17,9,16,7,8], which allow for the generation of reproducible and quantitative elasticity maps. In this paper, Supersonic Shear Wave Imaging (SSI) [8] is used to map the stiffness of the uterus during the myometrium contraction.…”
Section: Introductionmentioning
confidence: 99%
“…This technique, in which strain maps of tissues are calculated after applying static stress directly onto the surface of the body with the ultrasonic probe, provides information on the relative stiffness of the tissues investigated, but is highly operator dependant and non-quantitative. Such drawbacks can be overcome by using dynamic elastography techniques [17,9,16,7,8], which allow for the generation of reproducible and quantitative elasticity maps. In this paper, Supersonic Shear Wave Imaging (SSI) [8] is used to map the stiffness of the uterus during the myometrium contraction.…”
Section: Introductionmentioning
confidence: 99%
“…Nine of these subjects were not experiencing bleeding at the time of surgery (the "unripened" group), 6 were experience bleeding or dysmenorrhea (painful menstruation; the "uterine bleeding" group), and 7 subjects were given misoprostol, a prostaglandin agent used to soften the cervix prior to many gynecologic procedures, 10-12 hours prior to surgery (the "misoprostolripened" group). The "uterine bleeding" and "misoprostolripened" groups were combined based on statistical equivalence into a single "ripened" group (n = 13) [12], [13]. All subjects provided informed consent, and all work was HIPAA compliant and approved by the IRBs at Intermountain Healthcare and the University of Wisconsin.…”
Section: A Patient Populationmentioning
confidence: 99%
“…Studies have shown that as the delivery time approaches the collagen rich cervix is filled with water and enzymes which results in a lower attenuation value and a softening of the cervix as it prepares for delivery [23][24][25]. Our earlier work showed that attenuation of the cervix decreased as the cervix prepared for delivery [8][9][10][11][12] while the softening of the cervix can also be quantified using shear wave elastography [13][14][15].…”
Section: Introductionmentioning
confidence: 95%
“…Our earlier work showed that attenuation of the cervix decreased as the cervix prepared for delivery [8][9][10][11][12]. The softening of the cervix can also be quantified using shear wave elastography [13][14][15]. In this method a stress is created and then the strain in the tissue is observed from that stress.…”
Section: Introductionmentioning
confidence: 99%